Inter vehicle communication system for collision avoidance - Nurul Hazlina, Noordin; Hui, Althea C. Y.; Nurulfadzilah, Hassan; Rosdiyana, Samad (Springer Singapore, 2019)
In inter vehicle communication, there are many aspects that must be taken into considerations. The utmost important aspect is the speed of sending data packet, which is the key factor in preventing emergency message delay in traffic network. Other than that, the accuracy in reading and processing sensors’ data by microcontroller are essential in cases of collisions avoidance. The aim of this paper is to overcome the communication problems between vehicles located at intersection. In this paper, two conditions have been proposed: vehicle-to-vehicle (V2V) communication and vehicle-to-infrastructure (V2I) communication. Experiments have been conducted using prototype cars. The results show that the prototype cars are able to avoid collision through activation of communication system at certain section on the road.